Troll Fell - Langrish, Katherine (London : HarperCollins Children's Books, 2005)
Forced to move to Troll Fell to live with his uncles, Baldur and Grim, after his father's death, young Peer Ulfsson learns of his uncles' sinister plan to sell children to the trolls and sets out with an adventurous neighbor girl named Hilde to stop them.
6.0
5-8.
5-8
Keywords: Fantasy; Orphans -- Fiction; Trolls -- Fiction; Twins -- Fiction; Uncles -- Fiction; Vikings -- Fiction; Orphans -- Fiction; Trolls -- Fiction; Twins -- Fiction; Uncles -- Fiction; Vikings -- Fiction; Fantastic fiction